Congenital Dyserythropoietic Anemia Type II Diagnosed in a 69-Year-Old Patient with Iron Overload. Issue 5 (21st January 2016) - Greiner, Timothy C.; Patrick Burns, C.; Dick, Fred R.; Henry, Kathleen M.; Mahmood, Ijaz
Abstract : Congenital dyserythropoietic anemia type II is a rare disorder that is often diagnosed in patients before age 20 years. Patients with this disorder, which is also called hereditary erythroblastic multinuclearity associated with a positive acidified serum lysis test, may have symptoms of iron overload. The purpose of this case report is to alert physicians to consider the diagnosis of congenital dyserythropoietic anemia type II in elderly patients who have anemia and iron overload.